Comparative Evaluation of Germination Traits of Hybrid and Open Pollinated Tomato Varieties under Potassium Nitrate Seed Priming - Pantha, Aishwarya; Bhujel, Alisha; Pradhan, Ankita; Rijal, Purnima; Poudel, Shrisha; Kunwar, Rachana; Shrestha, Abhishek (Agronomy Journal of Nepal, 2025)
In order to assess the performance of two tomato varieties, Srijana and Suman, under seed priming with potassium nitrate (KNO₃) at four different concentrations 0%, 0.5%, 1%, and 1.5% the experiment was conducted in the Agronomy Laboratory of the College of Natural Resource Management, Bardibas, Mahottari. Three replications of the two types were set up in a completely randomized design. A number of metrics, such as germination percentage, mean germination rate, mean germination duration, root and shoot length, root-to-shoot ratio, and vigor index, were used to evaluate seed performance. Two-way ANOVA was used to evaluate the data.  The length of the roots and shoots varied significantly across treatments, according to the data.  The Srijana variety performed better than the others overall, with a germination rate of 90.67%, a mean germination duration of 4.67 days, a root length of 4.88 cm, and a shoot length of 6.43 cm. The best priming treatments were 0.5% and 1% KNO₃. These findings demonstrate how many tomato cultivars respond to seed priming and demonstrate how KNO₃ priming can improve early seedling growth and germination, ultimately leading to higher tomato output.